Asymptomatic bacteriuria in pregnant mothers: a valid and cost-effective screening test in Bangladesh - Ullah, Anayet A.; Barman, Arunodaya; Ahmed, Iftikhar; Salam, Md. Abdus (Informa UK, Ltd., 2012)
In Bangladesh, a number of screening tests for asymptomatic bacteriuria in pregnancy are in practice. The objective of this study was to assess the validity and cost-effectiveness of these screening tests. A total of 600 apparently healthy pregnant mothers were included in this study. The validity of the screening tests was calculated against the urine culture as ‘ gold standard ’ . Incremental cost-effective ratio between the screening test methods and the least costly method (microscopic urine analysis) was calculated. Bacterial count/oil-immersion field in Gram-stained smear of urine was the most sensitive (91.7%) and specific (97.2%). Incremental cost per additional positive cases of bacterial count, leukocyte esterase and combination of leukocyte esterase and nitrite were US $ 3, US $ 25 and US $ 23, respectively. Gram staining may be the alternative approach to traditional routine urinalysis for the screening of asymptomatic bacteriuria during pregnancy in clinical practice in Bangladesh, as well as other developing countries.